Con: should asymptomatic patients with moderate-to-severe OSA be treated?. Issue 1 (March 2019) - Vakulin, Andrew; Chai-Coetzer, Ching Li; McEvoy, R. Doug
The population prevalence of obstructive sleep apnoea (OSA) has increased significantly in the past 20–30 years paralleling trends in population ageing and increasing rates of overweight and obesity. A recent community-based study estimated that 84% of men and 61% of women have an apnoea–hypopnoea index (AHI) of >5 events·h −1 of sleep, with moderate-to-severe OSA (AHI >15 events·h −1 ) occurring in approximately 50% of men and 23% of women [1]. The most widely recognised manifestation of OSA, and the main target for treatment, is excessive daytime sleepiness. However, the majority of individuals with OSA in the general community [2] and even in sleep clinics [3] do not exhibit excessive sleepiness. This raises the important question of whether such patients should be treated. In a large proportion of patients with moderate–severe OSA who do not report daytime sleepiness there is no convincing evidence at present that CPAP or similar treatments provide benefit for associated medical disorders, such as hypertension and diabetes http://ow.ly/qqqi30nok4d